Determinan pendapatan pedagang kelontong di Kabupaten Tanjung Jabung Barat: (Studi Kasus Kecamatan Tebing Tinggi) - May Kristiani Simarmata; Rahma Nurjanah; Dwi Hastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to identify and analyze the socioeconomic characteristics of grocery store traders in Kabupaten Tanjung Jabung Barat (a case study in Kecamatan Tebing Tinggi) and to examine the factors influencing their income. The research method used in this study is a survey method with a quantitative approach. Data were collected through direct interviews with 67 grocery store traders at the research site. The results of the study show that initial capital, business duration, business location, and accounts receivable have a positive and significant effect on the income of grocery store traders, while working hours have no significant effect on income. The data analysis further indicates that the coefficient of determination (R²) is 0.3742, which means that 37 percent of the variation in traders’ income is explained by the variables in this study, while the remaining 63 percent is explained by other variables outside the research.